The Overview of Mother's Characteristics, Exclusive Breastfeeding History and Immunization Status on the Morbidity of Infants 1-14 Months in Sukabumi - Lani Gumilang; Rahmy Nurmalasari; Meita Dhamayanti; Dini Saraswati Handayani; Didah Didah (Faculty of Medicine, Universitas Andalas, 2019)
Morbidity among children in Indonesia is high. Based on the 2013 Hospital Information System data, there were five major morbidities, namely acute respiratory tract infections, diarrhea, fever, seizures, and pneumonia. This study aimed to describe the characteristics of mothers, history of exclusive breastfeeding and immunization status against morbidity in infants aged 1-14 months in the Sukabumi region. This study used descriptive research method with a cross-sectional study design on 71 mothers who have infants aged 1-14 months and are domiciled in the Sukabumi region. The data sources used were primary and secondary data, while the data was analyzed using univariate. The results of the study showed that the majority of mothers aged 20-35 years had infants morbidity due to fever by 78.9%, 29.6% of infants morbidity in mothers with elementary school graduate was caused by fever, housewives had infants morbidity due to fever by 78.9%, 83.1% of infants morbidity due to fever was occurred in mothers who performed exclusive breastfeeding, and 63.4% of morbidity in infants with complete immunization were also caused by fever. The results of this study can be concluded that the majority of morbidity was caused by fever, in mothers aged 20-35 years, mothers with elementary school graduate, housewife, children who obtained exclusive breastfeeding and complete immunization.